#### Answer

$$g(k^{2})=2k^{2}-3$$

#### Work Step by Step

$$g(x)=2x-3$$
To find $g(k^{2})$, substitute $k^{2}$ for $x$.
$$g(k^{2})=2k^{2}-3$$

Published by
Pearson

ISBN 10:
0321749006

ISBN 13:
978-0-32174-900-0

$$g(k^{2})=2k^{2}-3$$

$$g(x)=2x-3$$
To find $g(k^{2})$, substitute $k^{2}$ for $x$.
$$g(k^{2})=2k^{2}-3$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.